Psychological selection and optimal experience across cultures social empowerment through personal growth - Delle Fave, Antonella; Massimini, Fausto; Bassi, Marta; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Studies on well-being derive from two main perspectives: hedonism and eudaimonism. The former emphasizes the human search for pleasure and satisfaction while the latter focuses on fulfillment of one's true nature that includes both self-actualization and commitment to socially shared goals. Operating under the eudaimonic approach, Psychological Selection and Optimal Experience Across Cultures uses recent advancements in positive psychology to explore the connections between personal well-being and social welfare. People grow and live in cultures that deeply influence their values, aspirations and behaviors. However, individuals in their turn play an active role in building their own goals, growth trajectories and social roles while at the same time influencing culture trends. This process, known as psychological selection, is related to the individual pursuit of well-being. People preferentially select and cultivate in their lives activities, interests and relationships associated with optimal experience?a state of deep engagement, concentration and enjoyment. Several cross-cultural studies confirm the positive and rewarding features of optimal experience, and based on these evidences this book highlights the interplay between individual and cultural growth trajectories, ultimately conveying the core message that educating people to enjoy engagement and involvement in activities that can be relevant and meaningful for social welfare is a premise to foster the harmonious development of human communities and the peaceful cohabitation of cultures. Interest in eudaimonia has grown rapidly, especially in the past five years. Given this book's emphasis on the role of individuals as active agents in shaping their cultural environment and in promoting both their own development and cultural complexity, it fills a unique place in the increasing demand for studies in the field. Aimed at researchers and students in Psychology, Education, Health and the Social Sciences, it is useful for anyone interested in the promotion of individual happiness and well-being.
Introduction -- Part I Theory and methods -- Chapter 1: Hedonism and eudaimonism in positive psychology -- Chapter 2: Biology, culture and human behavior -- Chapter 3: Psychological selection and optimal experience -- Chapter 4: Instruments and methods in flow research -- Chapter 5: The phenomenology of optimal experience in daily life -- Chapter 6: Optimal experience and meditation: Western and Asian approaches to well-being -- Part II Applications -- Chapter 7: Optimal experience across cultures -- Chapter 8 Work: A paradox in flow research -- Chapter 9: Free time: an opportunity for growth, recreation, or stagnation -- Chapter 10: Relationships: safe harbor for flow explorers -- Chapter 11: Education, learning and cultural transmission -- Chapter 12: Optimal experience and religious practice -- Chapter 13: Acculturation and optimal experience -- Chapter 14: Flow and health: a bio-psycho-social perspective -- Chapter 15: Psychosocial maladjustment and mimetic flow -- References -- Epilogue.
Electronic reproduction.
Keywords: Psychology, Applied; Quality of Life; Positive psychology; Electronic books